Radio maps for fingerprinting in indoor positioning - Meneses, Filipe (2019)
In spite of all the efforts done by researchers, today we still do not have a universal and ubiquitous solution for indoor positioning. Fingerprinting is one of the most well-known technologies used to build indoor positioning systems, using the radio signals to determine the user or device location, exploring the principle that each location has a different radio signature. Radio maps are mandatory to implement a fingerprint indoor positioning solution. In this chapter we explore some of the key challenges raised when building and updating radio maps. We also explore some techniques that can be used to increase the radio map density, which could lead in some cases to more accurate results, and to filtering radio maps, by removing data that will not influence the quality of the position estimation but may influence the positioning engines performance. In the end, we discuss why the lack of standards may be influencing the slow deployment of indoor positioning systems in real-world.